Prediction of Stature Based on Foot Length In Medical Students of Birat Medical College & Teaching Hospital, Morang, Nepal - Mehta, Umesh Kumar; Dhakal, Arun; Parajuli, Surya B.; Shah, Sanjib Kumar (Birat Journal of Health Sciences, 2019)
Introduction: Stature is one of the most important anatomical parameters for personal identification. Estimation of stature by measuring different parts of the body is valuable in medico legal investigations as well as in anthropology.Objectives: The objective of this study was to find correlation between stature and foot length and developing a regression equation for stature estimation from foot length among medical students of Birat Medical College & Teaching Hospital, Morang, Nepal.Methodology: This is cross sectional study conducted at Department of Anatomy of Birat Medical College & Teaching Hospital, Morang, Nepal from 15 March 2019 to 15 June 2019. Two hundred (100 male and 100 female) medical students were enrolled in the study. Stature and foot length were measured using standard instruments. The collected data was entered into Microsoft excel and analyzed by using SPSS.Results: The mean stature in male was 165.4 cm with SD of 8.46 cm, in female the mean stature was 156.5 cm and with SD 6.56 cm. The mean foot length in male was 25.84 cm with SD of 1.73 cm, in female mean foot length was 23.35 cm with SD 1.30 cm. This gender wise difference in mean stature and foot length between males and females was statistically significant (p